Halal Tourism Requirements in Iran: Attraction for Muslim Tourists or Barrier for Non-Muslim Visitors? - Siyavooshi, Malihe; Keshavarzi, Sakine (Jurnal Internasional Penelitian Bisnis Terapan, 2025)
This study aims to investigate the importance of halal-friendly destination criteria on attracting Muslim tourists and the attitude of non-Muslim tourists towards the requirements of halal-friendly destinations. Also, the satisfaction and loyalty of Muslim and non-Muslim tourists to Iran destination were compared. The statistical population of the study is tourists entering Iran between 2010 - 2023. The data were collected by sharing a link to a trilingual questionnaire (Persian, Arabic, and English) on social networks and were analyzed using SPSS software. Data collected from 178 Muslim and 131 non-Muslim tourists from 51 different countries show that halal tourism criteria have great importance in choosing a tourist destination by Muslims. On the other hand, are not a major obstacle to attracting non-Muslim tourists. Satisfaction and loyalty were high in both groups of tourists. There was no significant difference between Muslim and non-Muslim tourists’ loyalty to halal tourism destinations, but Muslim tourists’ satisfaction was lower than that of non-Muslim tourists when traveling to Iran. The findings suggest that Muslim-majority countries with halal tourism infrastructure can work to attract both Muslim and non-Muslim tourists. However, it should be noted that Muslim tourists demand higher standards of halal tourism when traveling to such countries.